The association between the quality of life and depression of elderly in a nursing home institutional setting (Journal of Health Sciences, 2016)
Introduction: The quality of life is perceived individually and subjectively. The quality of life of elderly people in nursing home nursing homes depends on the degree to which their needs are fulfilled. The need to adapt to a new environment in an older age is a risky situation and may result in depression. The aim of the study was to analyze the change of quality of life and level of depression, as well as possible association of quality of life and level of depression, in elderly people admitted for the first time to nursing home.Methods: The research included 38 participants (10 men and 28 women). The data were obtained using the Geriatric Depression Rating Scale Short Form (GDS-SF) and a short form of the Quality of Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q-SF).Results: The average age was 79.2 (SD = 6.9) with a variation span of 30 years, minimum age was 62 (n = 1) and maximum age was 92 years (n = 1).The participants experienced a clinically significant reduction in depression symptoms, moving from a mild depression zone (8-12 points) to the zone of clinical standard (7 points or less). An essential finding was a strong negative correlation between the quality of life and depression.Conclusions: Obtaining information on depression and the quality of life of elderly in nursing home settings should be introduced as a standard part of nursing activities in order to improve the quality of customer care in the nursing homes.